Pengaruh Perilaku Organisasi, Kompetensi Kepribadian, dan Adaptasi Guru terhadap Mutu Pembelajaran Sekolah Dasar - Adliroh Adliroh; Maryanto Maryanto; Ghufron Abdullah (Cetta: Jurnal Ilmu Pendidikan, 2026)
The quality of learning in public elementary schools in Ungaran Timur District has not yet reached optimal and equitable levels, as reflected in disparities in achievement among schools and the relatively low levels of organizational behavior, personality competence, and teachers’ adaptability in supporting effective learning. This study aims to analyze the influence of organizational behavior, personality competence, and teacher adaptability on learning quality in public elementary schools in Ungaran Timur District, Semarang Regency, both partially and simultaneously. This research employed a quantitative approach with a correlational design. The population consisted of 235 teachers, with a sample of 148 teachers selected using proportional random sampling. Data were collected through questionnaires and analyzed using classical assumption tests, as well as simple and multiple linear regression analyses. The results indicate that all three independent variables have a positive and significant effect on learning quality. Partially, organizational behavior contributes 50.90%, personality competence 36.10%, and teacher adaptability 34.3%. Simultaneously, these variables contribute 69% to learning quality. These findings confirm that improving learning quality is inseparable from the support of a conducive organizational environment, strong teacher personalities, and the ability to adapt to the dynamics of educational change, including the implementation of the Independent Curriculum. In this context, learning quality is reflected through several key dimensions: classroom management, learning methods, and psychological support. The novelty of this research lies in the comprehensive integration of organizational environmental factors, teacher personality, and adaptability to educational change in improving learning quality. This research does not only highlight aspects of teacher leadership or technical competence in isolation, but also combines these with the implementation dimensions of the Independent Curriculum, which is still relatively new in the context of Indonesian education.